Study on the Prescribing Patterns of Drugs Used in Heart Failure - Baskota, Mitu; Rao, B.S.; Shakya, Rajani (Kathmandu University Journal of Science, Engineering and Technology, 2006)
Heart failure is the common cardiovascular diseases among people of south Asian Origin including Nepal. The prevalence of Heart failure increases with age and accounts for most of the adult hospital admissions. The objective of the study was to study the prescribing patterns of drugs used in the heart failure. The study included both the in-patients and outpatients conducted at 2 different hospitals inside the Kathmandu valley and one outside the valley, Dhulikhel. The period of study was nearly four months and the number of patients included was 156, which included total of 71 Males (52.59 %) and 64 Females (47.4%). Subjects of age groups 45-65 (45%) were found to be more susceptible to heart failure. Significant age, smoking & alcohol use, associated disease family history of disease related factors in the prevalence of heart failure were seen. The various drugs used frequently were, Diuretics, Cardiac glycosides, ACE-I, A II Receptor Blockers and Anti-Coagulants with respect to overall utilization. In the combination of drugs, was ACE-I +Diuretics + Digoxin was used most frequently. ACE-I was not appropriately prescribed as per the literature facts that they have various benefits in the treatment of congestive Heart failure and hence was underused. Ramipril, Lisinopril were also considered in the prescriptions in spite of their new entries. ARB, though similar in properties to the ACE accounts for a very small proportion of drug use profile, where high cost and lower availability may be accounted. Beta-blockers were also prescribed extensively.